Osseointegration of dental implants without primary stability: an experimental study in sheep - Shihab, Omed Ikram; Samad, Abduljaleel Azad; Ali, Hozak Zahir; Omer, Othman A.; Haider, Ahmed A. (Zanco Journal of Medical Sciences (ZJMS), 2017)
Background and objective: Primary implant stability is considered necessary for achieving and maintaining osseointegration. This experimental study aimed to evaluate the outcome of implants without primary stability, clinically and radiographically. Methods: Two adult sheep (3-4 years of age), 70 kg in weight, were included in the study. After sedation and local anesthesia, the lateral side of the basal bone of mandible is exposed by a single long incision. The implant bed performed in the inferior border of the basal bone of mandible drilling to 5 mm in diameter and 10 mm in length. Five implants were inserted into the basal bone of mandible for each side (right and left), but the sizes of inserted implant was 3.8 mm in diameter and 10 mm in length, after 4 months the 2 sheep were sacrificed and the universal torque ratchet was used to measure the stability of the implant by a counter torque 30 N/cm test. Cone Beam Tomography (CBCT) was used to evaluate the implants radiographically. Results: Nineteen (from 20) implants successfully tolerated a 30 N/cm countertorque test comprising (95%). Only one implant failed to osseointegrate (5%). During the healing period, no any adverse clinical signs reported. Conclusion: Dental implants may have a chance to osseointegrate even in the lack of primary stability.